FREE RADICAL SCAVENGING ACTIVITY OF VARIOUS EXTRACTS OF WHOLE PLANT OF Calycopteris floribunda (Lam.): AN IN-VITRO EVALUATION - Santharam, Bhuvaneswari; P, Ganesh; R, Soranam; Lekshmi, Packia (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: The present research was subjected to screen the free radical scavenging activity of various extracts of whole plant of Calycopteris floribunda by different in-vitro models. Methods: The antioxidant activity was evaluated by hydroxyl radical scavenging activity, nitric oxide radical scavenging activity with reference standard ascorbate and total phenol content respectively. Results: An inhibitory concentration 50% (IC50) value was found ethyl acetate extract of C. floribunda is more effective in hydroxyl radical scavenging activity than that of methanolic and petroleum ether extract. The IC50 values of ethyl acetate extract of C. floribunda and ascorbate were found to be 530 Î¼g/ml and 410 Î¼g/ml respectively. The ethyl acetate extract of C. floribunda was found more effective in the nitric oxide scavenging activity. The IC50 values of ethyl acetate extract of C. floribunda and ascorbate were found to be 570 Î¼g/ml and 410 Î¼g/ml respectively. But when compared to all the three extracts with ascorbate (standard), the ethyl acetate extract of C. floribunda showed the better result. In addition, the ethyl acetate extract of C. floribunda was found to contain a noticeable amount of total phenols, which play a major role in controlling antioxidants. The results were observed in a concentration dependent manner. Conclusion: Our findings revealed that ethyl acetate extract of C. floribunda possesses interesting antioxidant activity, which may provide production against free radicals induced damage to biomolecules. Keywords: Calycopteris floribunda, Antioxidant, Ascorbate, Scavenging activity, Inhibitory concentration 50%.